INFLUENCE OF KEY FACTORS ON CONTEMPORARY AGROTOURISM EFFICIENCY: A COMPREHENSIVE ANALYSIS (Conferencea, 2023)
This study assesses pivotal factors influencing contemporary agrotourism development's efficiency. Through a survey encompassing 120 agrotourism entities in the Fergana, Tashkent, and Jizzakh regions, this research delves into the organizational and managerial aspects shaping the agrotourism industry. The survey, designed to gauge the impact of these factors on industry efficiency, reflects opinions obtained from participants. Factors were meticulously selected based on industry analysis, developmental characteristics, and expert insights. Additionally, the study outlines a second model, proposing the expansion of agrotourism businesses in terms of scale, envisioning the establishment of substantial infrastructure within rural areas. This model entails the creation of specialized private hotels, cultural centres, and demonstration production hubs. Furthermore, it explores the potential of forming integrated agrotourism complexes through public-private partnerships, aiming for rapid industry development. The study concludes by recommending priority directions to enhance agrotourism processes, management strategies, and coordination among influencing factors. Implementation of these recommendations is poised to mitigate risks and foster the effective organization and management of agrotourism activities in the future.